Effect of sawdust species and particle size on xylose production - Suharti, Md Ishak (2012)
Xylose is a pentose sugar and commonly hydrolyzed from lignocellulosic material.This study was carried out to identify the species and particle size on xylose production was investigated.Three types of hardwood species (Meranti, Keruing and Resak) and five differences particle size of sawdust (800,615,400,315 and 200 µm) were used in the production of xylose.Hydrolysis method by using diluted sulfuric acid was employed.The sawdust was reacted with diluted sulfuric acid to degraded the hemicellulose from lignocellulosic structure.The higher xylose concentration that produced was 32.12 g/l.The overall results indicated that the sawdust species and particle size were Keruing and 400µm respectively exhibited the highest concentration of xylose due to the acid hydrolysis effects.From the Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM),the structure of treated sawdust was change.The maximum xylose production from sawdust was produce at 3.24% sulfuric acid concentration and reaction time 60 minutes.